Solve the equation in any way. 15 * (a-4)=42+8 * (a-4) (y+1) *18=36+12 * (y+1) (k+5) of *7-54= (k+5) *4 17 * (with-2)-36=19+ (with-2) *12

278
Answer the answer the answer the answer 1)15 * (and-4) =42+8 * (and-4) 2) (at +1)*18=36+12 * (at +1) 15a-60=42+8a-32 18u +18=36+12u +12 15a-8 =10+60 to a 18u-12 =48-18 7a =70 6u =30 and =70/7 at =30/6 and =10 at =5 _______________________________________________ 3) (k+5) of *7-54= (k+5) *4 4) 17 * (with-2)-36=19+ (with-2) *12 7k+35-54=4k+20 17s-34-36=19+12s-24 7k-4k=20+54-35 17s-12s =-5+34+36 3k=39 5s =65 k=39/3 from =65/5 k=13 with =13
88
Answer add